Would an Energy Conservation Nudge in Hotels Encourage Hotel Guests to Conserve?. (May 2016) - Chang, Howook "Sean"; Huh, Chang; Lee, Myong Jae
Utility companies achieved an average reduction of 2.5 percent in home energy use through an energy conservation nudge that provides feedback on energy consumption as compared with neighbors. This study investigated whether hotels can replicate this effect with their guests. A 2 (valence of electricity consumption) × 2 (comparison subject) experimental design with a control group was used with 1, 000 respondents reporting their behavioral intentions in response to the energy conservation nudge in a scenario-based experiment. The results of a one-way analysis of variance (ANOVA) revealed that behavioral intentions toward electricity conservation were pronounced when the nudge was provided (regardless of the valence of electricity consumption and the comparison subject). The results of an analysis of covariance (ANCOVA) with an energy conscious level as a covariate confirmed the effectiveness of the nudge on electricity conservation. The results indicate that hotels can achieve guest-driven electricity efficiency when an appropriately designed nudge is supplied to guests. The implications of the study are also discussed.